PERAN UNITED NATIONS CHILDREN’S FUND (UNICEF) DALAM MEMBERIKAN BANTUAN TERHADAP ANAK-ANAK KORBAN KRISIS KEMANUSIAAN DI MADAGASKAR TAHUN 2018-2020 - Adheila, Rahma Sari Putri; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research aims to determine the role of United Nations Children’s Fund (UNICEF) in providing assistance to children victims of humanitarian crisis in Madagascar. In an emergency and humanitarian context, children are the most suffering and most vulnerable communities. Madagascar's children are deprived of their rights, trapped in starvation, fell ill with life-threatening illnesses because their health, water and sanitation services and the infrastructure around them collapsed due to natural disasters. UNICEF as an international institution that works independently, becomes a forum to help fulfill the rights of Madagascar children.This study aims to find out how the role played by UNICEF in providing assistance to childrens in Madagascar in 2018-2020. This study uses the theory of the role of International Organizations and qualitative research methods with library research techniques, namely utilizing secondary data obtained through literature studies that get from various literatures such as books, journal, bulletins, annual reports of several related agencies, documents, or other materials that support research.The Humanitarian Action for Children program underline the role of UNICEF to help the children of Madagascar from all threats to their lives. The role that UNICEF has played is, reconstruction and revitalization efforts, and collaboration with the government and other organizations. Some of the activities held by UNICEF include distributing various needed assistance, providing mobile clinics, conducting campaigns and counseling, building temporary facilities, and providing psychosocial support. Keywords: Role, UNICEF, Humanitarian Crisis, Children